Optimalisasi Pemeriksaan Kesehatan (TTV, Gula Darah, Pemberian Vitamin) melalui Pendekatan Manajemen Keperawatan di Desa Bongan, Tabanan - Sukmayanti, Luh Putu; Suwandi, Cucuk; Ni Ketut Devy Kaspirayanthi; Satriawan, I Putu Ditha (Jurnal Abdi Mahosada, 2026)
Health check-ups in rural areas often face access constraints and poorly managed management, particularly in Bongan Village, Tabanan, where the prevalence of vital signs and blood sugar disorders is often overlooked. This community service activity aims to optimize services through a management approach that includes blood pressure-pulse-temperature (TTV) checks, blood sugar checks, and vitamin provision to village residents. The implementation method included participatory planning with the community health center, service implementation at Bongan 3 Elementary School for three days (July 4-6, 2025), and post-activity evaluation through brief interviews. The results showed that 80 participants were served, with abnormal TTV in 35 participants with hypertension (blood pressure results 150/70 mmHg-180/80 mmHg), blood sugar >126 mg/dL in 23 participants, and 100% of vitamin distribution, as well as education on hypertension and diabetes mellitus. This approach has proven effective in raising public health awareness about hypertension and diabetes mellitus.